Etiological Clinical and Laboratory Profile of Children admitted with Febrile Seizures in a Tertiary Care Hospital of Western Nepal - Laxman Paudel; Arun Pokhrel; Sumina Shrestha; Dipim Gautam (Med Phoenix, 2026)
Introduction: Febrile seizures are the most common seizure disorder in childhood and are a frequent cause of hospital admission. Information regarding the demographic, clinical, etiological, and laboratory characteristics of febrile seizures in Nepal remains limited. This study aimed to evaluate the demographic, etiological, clinical, and laboratory profile of children admitted with febrile seizures in a tertiary care hospital in Western Nepal.Materials and Methods: A hospital-based prospective observational study was conducted at Siddhartha Children and Women Hospital, Butwal, from September 2023 to September 2025. Children aged 6–60 months admitted with febrile seizures were enrolled consecutively. Demographic characteristics, clinical features, etiological diagnosis, and laboratory parameters were recorded. Febrile seizures were classified as simple or complex according to standard criteria. Data were analysed using SPSS version 26. Descriptive statistics were used to summarize the data, and the Chi-square test was applied to assess associations between variables. A p-value